Legalitas Perjanjian Kerja bagi Pekerja Informal dan Pekerja Gig Economy di Kota Medan - Nanci Yosepin Simbolon; Alusianto Hamonangan; Ria Sintha Devi; Ramsi Meifati Barus; Herdi Munte; Novi Juli Rosani Zulkarnain; Darwin Sinabariba; Seri Mughni Sulubara (Jurnal Kabar Masyarakat, 2026)
This community service activity examines the legality of employment agreements involving informal workers and gig economy workers in Medan City amid the rapid growth of the digital economy. The study focuses on the form, content, and legal implications of employment agreements, as well as the extent to which such agreements provide protection for workers who possess weak bargaining positions. The method employed is a socio-juridical approach with qualitative analysis through literature studies on laws and regulations, related academic references, and interviews with gig economy workers, informal workers, and other relevant parties. The findings indicate that although most employment agreements formally fulfill the legal requirements under civil law, materially they tend to be unbalanced by positioning workers as “partners” without adequate labor rights protection. In the non-platform informal sector, employment relationships are generally based only on verbal agreements that do not clearly regulate rights, obligations, or dispute resolution mechanisms. The low level of workers’ legal literacy also contributes to their limited understanding of contractual provisions. Therefore, strengthening legal literacy, developing fairer employment agreement models, and formulating more responsive policies are necessary to ensure proper legal protection for informal and gig economy workers.